Geostrophic currents in the Antarctic zone of the Indian Ocean - Keiji Nasu; Mikio Naganobu (National Institute of Polar Research, 1981)
The research ship KAIYO MARU (Jap. Fish. Agency) occupied 36 oceanographic stations between 61°and 65°S and between 110°and 120°E during the period from January 13 to 29,1980. Dynamic topography and corresponding currents were computed with reference to the 1500-decibar surface. Eastward flow is dominant in the survey area, including the cyclonic and anticyclonic eddies in the area between 62°and 63°20'S and between 105°and 110°E. Cyclonic and anticyclonic circulations are also existing along 120°E. A strong meandering of eastward flow is recognized south of 63°S, which must be influenced by the bottom configuration. The velocity of geostrophic current, relative to the 1500-decibar surface, north of 64°20'S in the survey area gradually decreased toward the deep layer. But it increased south of 64°20'S, giving a maximum of 2.6cm s^ at 300-400m in depth, while the surface velocity is 0.3cm s^.